New Strategies in the Treatment of Plasmodium berghei Based on Nanoparticles: A Systematic Review - Shakib, Pegah; Marzban, Abdolrazagh; Mardanshah, Omid; Fallahi, Shirzad; Khan, Israr A.; Azarhazin, Mohammad; Cheraghipour, Kourosh (Current Pharmaceutical Biotechnology, 2023)
Background: Drug resistance is a current issue affecting parasites caused by Plasmodium. Therefore, researchers have expanded their studies on nanoparticles to find new and effective drugs that can treat drug-resistant strains. The present study systematically investigates the effect of different nanoparticles, including metal, polymer, and lipid nanoparticles, on Plasmodium berghei. Methods: In this study, English-language online literature was obtained from the databases Science Direct, PubMed, Scopus, Ovid, and Cochrane to conduct a systematic review. In the search, we used the keywords: (Plasmodium Berghei) AND (Malaria) AND (Parasitemia) AND (antimalarial activity) AND (nanoparticles) AND (Solid lipid NPS) AND (Nano lipid carriers) AND (Artemether) AND (Chloroquine) AND (intraperitoneal) AND (in vivo). Initially, a total of 160 studies were retrieved from the search. After removing duplicates, 80 studies remained. After reviewing the title and abstract of each study, 45 unrelated studies were eliminated. Results: The remaining 35 studies were thoroughly reviewed using the full texts. The final result was 21 studies that met the inclusion/exclusion criteria. Conclusion: Using these findings, we can conclude that various nanoparticles possess antiparasitic effects that may be applied to emerging and drug-resistant parasites. Together, these findings suggest that nanostructures may be used to design antiparasitic drugs that are effective against Plasmodium berghei.
Keywords: drug-resistant strains